2018
DOI: 10.1073/pnas.1801205115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular model of human tropoelastin and implications of associated mutations

Abstract: Protein folding poses unique challenges for large, disordered proteins due to the low resolution of structural data accessible in experiment and on the basis of short time scales and limited sampling attainable in computation. Such molecules are uniquely suited to accelerated-sampling molecular dynamics algorithms due to a flat-energy landscape. We apply these methods to report here the folded structure in water from a fully extended chain of tropoelastin, a 698-amino acid molecular precursor to elastic fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 42 publications
5
74
0
Order By: Relevance
“…The tropoelastin monomer represents the dominant building block for elastic fibers (cartoon representation of molecular structure is embedded in a SAXS‐derived outline, based on ref. ). Reproduced with permission .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The tropoelastin monomer represents the dominant building block for elastic fibers (cartoon representation of molecular structure is embedded in a SAXS‐derived outline, based on ref. ). Reproduced with permission .…”
Section: Introductionmentioning
confidence: 97%
“…The mature form of the secreted human tropoelastin monomer is 60 kDa and is composed of an alternating pattern of repetitive, hydrophobic glycine‐, valine‐, and proline‐rich domains spread out between lysine‐containing cross‐linking domains . Traditionally described as a largely disordered molecule, recent studies suggest that tropoelastin is a flexible molecule with a distinct nanostructure that determines its structural and cell‐adhesive properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the insertion or deletion of TE domains or the mutation of certain amino acid residues affects diverse mechanisms associated with the assembly of TE monomers into a polymeric network such as coacervation and cross‐linking processes as well as the resultant mechanical properties. This suggests that variations in the TE sequence allow tissue‐specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions …”
Section: Tropoelastin Domain Structure and Expressionmentioning
confidence: 99%
“…This suggests that variations in the TE sequence allow tissue-specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions. [15][16][17] TE's sequence is highly repetitive and about 80% are composed of the four amino acids Gly, Ala, Val, and Pro. The precursor has alternating hydrophobic and more hydrophilic domains, which are encoded by individual exons, so that the domain structure of the protein is reflected in the exon organization of its gene.…”
Section: Introductionmentioning
confidence: 99%